Colorful perovskite solar cells : progress, strategies, and potentials - Wang, Hao (2021)
In the past few years, a large variety of perovskite solar cells (PSCs) with vivid and well-distinguished color hues have been demonstrated. In this Perspective, we compare different strategies employed to realize colorful PSCs both in opaque and semitransparent designs. The approaches used to modulate the PSCs' colorful appearance can be divided into two main categories: the first one based on the modifications of their internal layers (i.e., absorber, electron- and/or hole-transporting layers, and electrodes), while the second is based on the addition of external colored or nanostructured films to the standard PSCs. The advantages and bottlenecks of each strategy are discussed in terms of PSCs' color tunability, transparency, photovoltaic performances, fabrication processes feasibility, and scalability, in view of suitable applications in an urban context for building-integrated photovoltaics.